Dialektika Hegel Kekhalifahan Umayyah Sebagai Pencegah Radikalisasi - Ramadhani, Muhammad Hanif; Ayundasari, Lutfiah (Jayapangus Press, 2024)
The background to this research is the discourse on Islamic history which is often monopolized to produce a single narrative regarding the history of a great and majestic Islamic civilization unlike today. This is often used as an argument for why we have to return to the time of the prophet and the caliphate, which led to radicalization, especially of young people, to restore the caliphate in Indonesia. Why are young people easily radicalized? What historical scholarship can be used to counter it? and What is the history of Islamic civilization that was not radicalized? The answer to this question is about the internal and external problems faced by today's young people, especially students. The way to overcome this is through critical and creative thinking as in the 2023 Merdeka Curriculum. This research aims to provide history teachers with a role in preventing radicalization through historical scholarship, namely the Hegel Dialectic, especially the history of Islamic civilization. This article uses qualitative research with the literature study method. This research analyzes the reasons why young people who are often targets of radicalization by terrorist groups become their members by comparing the present with the